2017
DOI: 10.1525/sod.2017.3.2.163
|View full text |Cite
|
Sign up to set email alerts
|

The Capitalist World-economy in the Longue Durée

Abstract: This article examines the global distribution of wealth within the capitalist world-economy over the longue durée. In stark contrast to the convergence of wealth predicted by modernization theory, the relatively stable bimodal (core-periphery) structure predicted by dependency theory, and the relatively stable trimodal (core-semiperiphery-periphery) structure, this article finds that the structure of the distribution of wealth in the world economy has transformed with each successive world hegemonic cycle. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 51 publications
1
18
0
1
Order By: Relevance
“…The question of the actual morphology of global hierarchy is again being hotly debated in the world-systems tradition and extending from it. Karataşli (2017), squarely in that tradition, has recently extended the Arrighi and Drangel contribution to posit a contemporary 'quadri-modal' distribution. Collections by Bond and Garcia (2015) and Wallerstein et al (2015) consider this question directly in the context of the rise of the so-called BRICS.…”
Section: Global Production Network As Conduits Of Unequal Value Distributionmentioning
confidence: 98%
“…The question of the actual morphology of global hierarchy is again being hotly debated in the world-systems tradition and extending from it. Karataşli (2017), squarely in that tradition, has recently extended the Arrighi and Drangel contribution to posit a contemporary 'quadri-modal' distribution. Collections by Bond and Garcia (2015) and Wallerstein et al (2015) consider this question directly in the context of the rise of the so-called BRICS.…”
Section: Global Production Network As Conduits Of Unequal Value Distributionmentioning
confidence: 98%
“…Unresolved Issues: Emerging Economies in the Semi-periphery Of final note, a degrowth agenda that expands to include a world-systems perspective would also recognize that not all countries outside of the core economies are in the same position -either in terms of their capacity to appropriate the surplus from exploited labor or ecological surplus. The multinationalization of production undergirds neoliberal globalization, and many formerly non-industrial economies now have substantial manufacturing sectors that are arguably best categorized as semi-peripheral (Karataşlı 2017). Some scholars have suggested that while such countries remain exploited by core economies, they also engage in exploitation of countries within the periphery including through ecologically unequal exchange and sub-imperialism (Bond 2018;Frame 2018Frame , 2022b.…”
Section: 4mentioning
confidence: 99%
“…World-systems theory has always had an important semi-periphery category, a category that contains both core and peripheral characteristics (Chase-Dunn 2013). In the contemporary world system, this category now includes industrializing, middle-income countries, also known as emerging economies, that were previously considered peripheral, such as a number of East Asian and Southeast Asian countries (Karataşlı 2017). Such emerging economies occupy a distinct, intermediate semi-peripheral status and, as such, face a number of complex, contradictory dynamics and pressures that drive ecological degradation both within and outside of their national borders.…”
Section: The Dynamics Of Ecological Imperialism In the Capitalist Wor...mentioning
confidence: 99%